Propionibacterium freudenreichii Surface Protein SlpB Is Involved in Adhesion to Intestinal HT-29 Cells - do Carmo, Fillipe L. R.; Rabah, Houem; Huang, Song; Gaucher, Floriane; Deplanche, Martine; Dutertre, Stéphanie; Jardin, Julien; Le Loir, Yves; Azevedo, Vasco; Jan, Gwénaël (Frontiers in Microbiology, 2017)
Propionibacterium freudenreichii is a beneficial bacterium traditionally used as a cheese ripening starter and more recently for its probiotic abilities based on the release of beneficial metabolites. In addition to these metabolites (short-chain fatty acids, vitamins, bifidogenic factor), P. freudenreichii revealed an immunomodulatory effect confirmed in vivo by the ability to protect mice from induced acute colitis. This effect is however highly strain-dependent. Local action of metabolites and of immunomodulatory molecules is favored by the ability of probiotics to adhere to the host cells. This property depends on key surface compounds, still poorly characterized in propionibacteria. In the present study, we showed different adhesion rates to cultured human intestinal cells, among strains of P. freudenreichii. The most adhesive one was P. freudenreichii CIRM-BIA 129, which is known to expose surface layer proteins. We evidenced here the involvement of these proteins in adhesion to cultured human colon cells. We then aimed at deciphering the mechanisms involved in adhesion. Adhesion was inhibited by antibodies raised against SlpB, one of the surface layer proteins in P. freudenreichii CIRM-BIA 129. Inactivation of the corresponding gene suppressed adhesion, further evidencing the key role of slpB product in cell adhesion. This work confirms the various functions fulfilled by surface layer proteins, including probiotic/host interactions. It opens new perspectives for the understanding of probiotic determinants in propionibacteria, and for the selection of the most efficient strains within the P. freudenreichii species.